Effect of Life Style, Price, and Halal Label on Consumers' Repurchase Interest of Mixue Ice Cream & Tea - Fadhillah Insani; Ika Darma Yuni; Chuzaimah Batubara (Universitas Pendidikan Indonesia, 2023)
This study aims to determine the effect of lifestyle, price, and halal labels on consumer repurchase intentions for Mixture Ice Cream Tea. This research was conducted in light of the fact that, in the last two years, there has been an increase in sales of Mixue products. Many things are the cause of this, one of which is the Mixue product, which is the current trend, so that the level of consumer purchases will be even higher. The data analysis technique uses multiple linear regression using the SPSS (Statitical Program for Social Science) program. The sample studied was 100 people. The technique used in sampling is the purposive sampling technique. The findings of this study are as follows: First, the life style variable has a positive and significant influence on the repurchase intention of Mixture consumers, with a calculated t value of 3.897. Second, the price variable has a positive and significant influence on the repurchase intention of Mixture consumers, with a calculated t value of 2.390. Third, the Halal Label variable has a positive and significant influence on Mixture consumer repurchase intention with a t-count value of 2.476.Â Keyword:Repurchase intensions,lifestyle, price, label halal, Mixue ice cream tea